An Interview with Mr. Mukesh Raj Kafle - Kafle, Mukesh Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
In light of ongoing discourses, at present, on prevailing energy crisis and the hydropower development in Nepal, HYDRO Nepal felt this an opportune moment to review and assess the present energy scenario of Nepal. This time, HYDRO Nepal takes pleasure in presenting an interview with Mr. Mukesh Raj Kafle, Managing Director, Nepal Electricity Authority with Mr. Upendra Dev Bhatta, Editor-in-Chief of HYDRO Nepal Journal. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 63-67